Bandwagon effects in social television: How audience metrics related to size and opinion affect the enjoyment of digital media. (June 2020) - Waddell, T. Franklin; Sundar, S. Shyam
Abstract: In this era of social television, we see not only the content of online videos but also how many other viewers are viewing them and how they are reacting to them. Do these metrics about audience size and opinion affect our own reactions? And, does it matter where these viewers are geographically located? We investigated these questions by first proposing a typology of audience cues based on size, opinion, and identity, and then testing the effects of each of these cues through a 2 (frequency metric: high number of viewers vs. low number) x 3 (evaluative metric: positive comments vs. negative comments vs. no comment control) x 2 (distance metric: low distance vs. high distance) between-subjects experiment (N = 410). We discovered that view counters and comments affect media enjoyment through perceptions of audience size and collective opinion respectively. Theoretical and practical implications are discussed. Highlights: Responses of other audience members affect our enjoyment of digital media content. New typology of audience metrics for social television—size, comments and identity. Negative comments affect perceived crowd opinion and indirectly reduce enjoyment. High view counters affect perceived crowd size and indirectly increase enjoyment. Audience metrics have an effect on enjoyment regardless of audience location.